Economic growth and investment in R&D: Contemporary challenges for the European Union - Hafezali Iqbal Hussain; Azlan Ali; Hassanudin Mohd Thas Thaker; Mohsin Ali (Contemporary Economics, 2020)
This paper presents new approaches to investigating economic growth and innovation activity as well as analyzing investment in R&D needs and efficiency in the context of contemporary challenges for European integration. Our research modeled the impact of R&D investment on GDP growth under broad conditions of globalization. In addition to capital and labor factors, we took into account factors that influence climate change, keeping in mind their relation to economic activity. Additionally, we paid particular attention to other factors driving sustainable economic growth, such as consumption of scarce resources as well as in- equality and poverty. Herein, we proposed new modeling conceptions for evaluating the impact of R&D investment on economic growth. The suggested method was adapted to analyze the case of development processes in the European Union. Our research confirmed the hypothesis that R&D expenditure has a positive impact on economic growth, and the impact is much higher in well-developed EU economies under condi- tions of sustainable economic development and globalization. The research was based on the case of the European Union economies. The panel least squares method was applied for the modeling and estimations.
Keywords: A10; E17; F01; F39; O39; 330; economic growth; R&D investment; European Union; sustainable development